Antagonist activity of Trichoderma sp. against Sarocladium oryzae on sheath rot disease of rice cultivation in vitro assays / Noor Irwani Abdul Hamid and Intan Sakinah Mohd Anuar - Abdul Hamid, Noor Irwani; Mohd Anuar, Intan Sakinah (Faculty of Plantation and Agrotechnology, 2018)
Rice (Oryza sativa) is one of the most important staple crops that were grown in 85% of the area under crop production in Malaysia. Some rice area in Malaysia was detected has been infected by sheath rot disease that using excessive fungicide to control the disease. Therefore, biological control is highly recommended when compare to other options for controlling many disease in rice. Thus, the objective in this study due to isolate Sarocladium oryzae and characterize based on morphological characteristics and to observe the inhibition of S. oryzae against Trichoderma sp. using dual culture method. In this study, the use of soil-born pathogen specimens Trichoderma sp. against four isolates of seed-born pathogen Sarocladium oryzae as a biocontrol agent. Both pathogens were distinct from each other in the characteristics of mycelial growth rate, colony appearance, shape of conidia and the conidiophores for microscopic and macroscopic examinations. This biological control is subsequently tested on antagonistic activity against S. oryzae by dual culture technique. It was found that Trichoderma sp. showed the ability to inhibit the isolate pathogen is more than 50 percent. Isolates SRO2 and SRO1 showed the highest inhibition percentages with 85.69% and 73.91% respectively. Trichoderma sp. can acts as biological control agent due to faster growing. As a conclusion, from the potential isolates found in this study will be further develop for coating rice seed with Trichoderma sp. which an alternative method to control sheath rot disease in the future.